Three essays on irrigated agriculture in Brazil - Morais, Gabriel Alves de Sampaio (2019)
The Irrigation technology is an important tool capable of mitigating the adverse effects of climate change, ensuring the yields, raising agricultural productivity rates and increasing employment in rural areas, which generates income and raises food security. Despite its multiple benefits, irrigation adoption in Brazil is still low given the potential for incorporation of new arable land, making the effects of this technology on the production process underestimated and underexplored. The present thesis seeks to analyze the effect of irrigation adoption on important aspects of the Brazilian irrigated agriculture, such as the technical efficiency between irrigators and rain-fed producers; the effect of irrigation on grain supply and demand for productive factors; and added gross revenue from the adoption of irrigation technology. To achieve those goals, three chapters are developed: Irrigation, technical efficiency and farm size in Brazil; Irrigation effects on grain sector in the Brazilian Southeast: A short-run analysis; and The value of irrigation adoption in the Brazilian agriculture. The first chapter analyzes the effect of irrigation technology adoption on the technical efficiency of Brazilian agricultural establishments. The methodological approach combines the stochastic production frontier structure, taking into account the selection bias (Heckman's approach), with the entropy balancing technique. The results show that irrigation adoption contributes to increasing the technical efficiency of irrigators by 2.51 percentage points compared to rain-fed farmers, on average. The greatest effect is observed for the group of large farmers. In the second chapter, we analyze the effect of irrigation on the supply of grains and the demand for productive factors in the Southeast region of Brazil. A system of equations is estimated using the restricted quadratic profit function approach. The results point toward a positive effect on the supply of grains and demand for labor. In addition, irrigation contributes to a 2.1% increase (US$ 83.45 million) in the average revenue generated by the grains analyzed. The third and last chapter aims to obtain a measure of value of the irrigation adoption in terms of gross added revenue when land is irrigated, relative to a non- irrigated land, using the production function approach. The results show an additional gross revenue due to irrigation of US$ 1,492.15/ha, on average, and the estimated value of irrigation for Brazilian agriculture is US$ 2.96 billion. The overall results provide useful information to design public policies that aim to develop irrigated agriculture in Brazil, such as the need for policies toward small producers regarding the provision of specialized technical assistance and rural credit services, as well as those related to water resources and rural electrification within the farm. In addition, the results may provide useful information that can assist water charging policies used in irrigation. Finally, I conclude that irrigation technology plays an important role in the technical efficiency of producers, in expanding the outputs supplies, in generating rural employment and gross revenue added to the agricultural sector. Keywords: Irrigation. Technical efficiency. Farm size. Grain supply. Revenue. Irrigation value.